CERCOSPORA BRUNFELSIICOLA (FUNGI, MYCOSPHAERELLACEAE), A NEW TROPICAL CERCOSPOROID FUNGUS ON BRUNFELSIA UNIFLORA - Iman Hidayat; Jamjan Meeboon (Research Center for Biology, 2014)
Cercospora brunfelsiicola on Brunfelsia uniflora is proposed as a new species based on a combination of molecular phylogenetic and morphological data analyses. The molecular phylogenetic analysis based on combined multilocus analyses of the Internal Transcribed Spacer (ITS), part of the elongation factor 1–a gene (EF1–a), and part of the calmodulin (CAL) gene regions showed that C. brunfelsiicola is phylogenetically distinguishable from other Cercospora species, including members of the C. apii s. lat. complex. Morphologically, C. brunfelsiicola differs from other closely related Cercospora species, in particular C. acaciae-mangii, by forming lesions with indistinct margin, larger stromata [(32) 48.5 ± 10.6 (68) ?m diam.], and filiform to narrowly obclavate conidia [(45) 59 ± 9.1 (72) × (2.5) 2.5 ± 0.2 (3) ?m].